The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0085-56262010000300001
|View full text |Cite
|
Sign up to set email alerts
|

The three phases of the ensemble forecasting of niche models: geographic range and shifts in climatically suitable areas of Utetheisa ornatrix (Lepidoptera, Arctiidae)

Abstract: ABSTRACT. The three phases of the ensemble forecasting of niche models: geographic range and shifts in climatically suitable areas of Utetheisa ornatrix (Lepidoptera, Arctiidae). Species' geographic ranges are usually considered as basic units in macroecology and biogeography, yet it is still difficult to measure them accurately for many reasons. About 20 years ago, researchers started using local data on species' occurrences to estimate broad scale ranges, thereby establishing the niche modeling approach. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
3
26
0
4
Order By: Relevance
“…Coefficients of PCA show high similarity between the carbon emission scenarios, as expected. The largest variation is associated to the modeling methods, in agreement with results of other studies that found SDMs as the main source of uncertainty (ARAÚJO et al, 2005a, b;DINIZ-FILHO et al, 2009a, 2010a. Moreover, it is also widely discussed in the literature that the SDMs tend to differ from each other in prediction of species distribution, both in the present and future scenarios (ELITH et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Coefficients of PCA show high similarity between the carbon emission scenarios, as expected. The largest variation is associated to the modeling methods, in agreement with results of other studies that found SDMs as the main source of uncertainty (ARAÚJO et al, 2005a, b;DINIZ-FILHO et al, 2009a, 2010a. Moreover, it is also widely discussed in the literature that the SDMs tend to differ from each other in prediction of species distribution, both in the present and future scenarios (ELITH et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…The use of a principal component analysis suggested by some authors (DINIZ-FILHO et al, 2010a;ARAÚJO et al, 2005b) was important to reveal qualitatively the contribution of each source of variation (SDMs, AOGCMs, emission scenarios) in maps resulted from ensemble forecast. Coefficients of PCA show high similarity between the carbon emission scenarios, as expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed (the nuts) are important for local economies, so understanding population and range dynamics under climate change may be also important for optimizing adaptive strategies for local human communities as well (e.g., Nabout et al, 2011). We used an ensemble forecast approach for obtaining species' range in which multiple SDMs and climatic models were combined (Marmion et al, 2009;Diniz-Filho et al, 2009a, 2010aNabout et al, 2010). We then obtained a series of genetic parameters (number of alleles per locus, expected heterozygosity under Hardy-Weinberg equilibrium (HWE) and mutation-drift equilibrium) for the entire species, which were recalculated assuming that local population in areas of low future environmental suitability will become extinct.…”
Section: Introductionmentioning
confidence: 99%
“…Alfred Russell Wallace (1823Wallace ( -1913 Since immemorial times, from Wallace to modern scientists, the study of the geographical distribution of species has fascinated humans. Many studies have focused on the evolution, dynamics, and structure of geographic ranges (Brown et al 1996;Gaston 2003;Diniz Filho et al 2010), but, albeit their theoretical relevance, estimating geographic ranges and species distribution is still a challenging issue for ecologists and biogeographers. Modern scientists have been developing statistical and mathematical models to infer and predict geographic distribution of species by coupling data on species occurrences at different spatial scales with environmental (bioclimatic) data (Pearson & Dawson 2003).…”
Section: Introductionmentioning
confidence: 99%